2022
DOI: 10.1037/abn0000746
|View full text |Cite
|
Sign up to set email alerts
|

Maternal prenatal infection and anxiety predict neurodevelopmental outcomes in middle childhood.

Abstract: Prenatal maternal infection and anxiety have been linked, in separate lines of study, with child neurodevelopment. We extend and integrate these lines of study in a large prospective longitudinal cohort study of child neurodevelopment. Data are based on the Avon Longitudinal Study of Parents and Children (ALSPAC) cohort; prenatal maternal anxiety was assessed from self-report questionnaire; prenatal infection was derived from reports of several conditions in pregnancy (n = 7,042). Child neurodevelopment at app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 77 publications
0
16
0
Order By: Relevance
“…These results support those of previous studies of acetaminophen use in pregnancy and child neurodevelopmental and behavioral outcomes, which reported the confounding effect of prenatal alcohol consumption [ 3 6 ]. Furthermore, previous studies have found an association between maternal infection and child development including an increased risk for autism spectrum disorders [ 42 , 43 ], social and communication problems [ 44 ], and emotional symptoms [ 45 ]. However findings have been inconsistent and some studies have not found an association, which may be due to differences in the covariates included in the models, the severity of infection [ 46 ], and differences in trimester of infection [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results support those of previous studies of acetaminophen use in pregnancy and child neurodevelopmental and behavioral outcomes, which reported the confounding effect of prenatal alcohol consumption [ 3 6 ]. Furthermore, previous studies have found an association between maternal infection and child development including an increased risk for autism spectrum disorders [ 42 , 43 ], social and communication problems [ 44 ], and emotional symptoms [ 45 ]. However findings have been inconsistent and some studies have not found an association, which may be due to differences in the covariates included in the models, the severity of infection [ 46 ], and differences in trimester of infection [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrate the robustness of the association between the level of salivary cortisol and the level of stress during pregnancy at different gestational ages [ 49 ]. These authors emphasize the importance of the salivary cortisol level, which can be an important predictor of child outcome because it may be the best indicator of HPA axis disturbances caused by maternal stress [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maternal prenatal psychological distress, which includes depression symptoms and anxiety, has been found to affect the offspring's neurodevelopment, including motor and cognitive development, temperament, and mental health through effects on the developing fetus; a process commonly known as the Developmental Origins of Health and Disease hypothesis. [1][2][3][4][5][6][7][8][9][10][11][12] The impact of maternal psychological distress during pregnancy on offspring development can depend on the offspring's developmental age and sex; however, research results in this regard remain inconsistent. There are also inconsistent findings regarding the periods of pregnancy during which maternal psychological distress has the greatest impact on the offspring.…”
Section: Introductionmentioning
confidence: 99%